The Cambridge companion to utopian literature - Claeys, Gregory (Cambridge companions to literature., 2010)
"Since the publication of Thomas More's genre-defining work Utopia in 1516, the field of utopian literature has evolved into an ever-expanding domain. This Companion presents an extensive historical survey of the development of utopianism, from the publication of Utopia to today's dark and despairing tendency towards dystopian pessimism, epitomised by works such as George Orwell's Nineteen Eighty-Four and Margaret Atwood's The Handmaid's Tale. Chapters address the difficult definition of the concept of utopia, and consider its relation to science fiction and other literary genres. The volume takes an innovative approach to the major themes predominating within the utopian and dystopian literary tradition, including feminism, romance and ecology, and explores in detail the vexed question of the purportedly 'western' nature of the concept of utopia. The reader is provided with a balanced overview of the evolution and current state of a long-standing, rich tradition of historical, political and literary scholarship"--